The potential of developing receptive and productive language skills in English language by playing English computer games - Martinová, Petra (Univerzita Pardubice, 2025)
This bachelor thesis focuses on the potential of developing receptive and productive language skills in English language by playing English computer games. The theoretical part of the thesis introduces features of informal learning as well as computer games. Aspects of computer games are presented together with two types of games, multiplayer games and single player games. Furthermore, language skills and strategies for their acquisition are examined in the first part of the thesis. The practical part revolves around three interviews and their analysis. The interviews were carried out to find out the players' experience with promoting English language skills thorough playing computer games.
Využití počítačových her v rozvoji řečových dovedností
Keywords: neformální vzdělávání; počítačové hry; hry pro jednoho hráče; hry pro více hráčů; řečové dovednosti; informal education; computer games; single player games; multiplayer games; language skills